Behavior of the magnetic subsystems in Nd2BaNiO5 - Popova, Elena; Klimin, S. A.; Popova, M. N.; Klingeler, Rüdiger; Tristan, N.; Büchner, B.; Vasil’ev, A. N. (Journal of experimental and theoretical physics, 2014)
The temperature dependences of the heat capacity, the magnetic susceptibility, and the splitting of the ground Kramers doublet of the Nd3+ ion in the chain magnet Nd2BaNiO5 are studied. An antiferromagnetic phase transition manifests itself as anomalies in all these dependences. The parameters of the Nd-Ni and Nd-Nd interactions are estimated. The field dependence of the magnetization has two anomalies. A strong magnetic anisotropy prevents the magnetic moments of the Nd3+ ion from deviating from axis c in the crystal even in an external magnetic field. The processes of magnetization and the internal specific features of a chain of spins S = 1 are discussed.